2022
DOI: 10.3390/atmos13071158
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Air and Sea Surface Temperatures in the Northern and Southern Part of the Adriatic Sea

Abstract: The paper compares air and sea surface temperatures in recent years on two islands in the Adriatic Sea. The data measured at the climatological station Krk on the island of Krk and the main meteorological station Lastovo on the island of Lastovo are used. The island of Krk is located in the north of the Adriatic Sea and Lastovo in the south. Since a significant increase in air and sea surface temperatures has been observed over the last thirty years, the goal is to establish how they reflect at these two stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…According to Branković et al [60], there is a statistically significant increase in the Croatian coastal zone, which has intensified within a shorter period, as evidenced by the recording of five to seven of the ten warmest years in the period of 2001-2010. Furthermore, a statistically significant increase in the annual maximum temperatures was also observed inland [61,62]. Perčec-Tadić et al [63] found stronger trends in the continental and mountainous regions.…”
Section: Analysis Of Air Temperature Dynamicsmentioning
confidence: 87%
“…According to Branković et al [60], there is a statistically significant increase in the Croatian coastal zone, which has intensified within a shorter period, as evidenced by the recording of five to seven of the ten warmest years in the period of 2001-2010. Furthermore, a statistically significant increase in the annual maximum temperatures was also observed inland [61,62]. Perčec-Tadić et al [63] found stronger trends in the continental and mountainous regions.…”
Section: Analysis Of Air Temperature Dynamicsmentioning
confidence: 87%
“…The climate is influenced by the Bora wind, which is known to be associated with cold and dry continental air [34]. The physicochemical processes are directly influenced by the inflow of water from the river Po in the north as well as its specific topography [35]. The Adriatic Sea has a lower salinity level than the rest of the Mediterranean due to the inflow of inland waters, which contain about a third of the freshwater that enters the entire Mediterranean Sea [35].…”
Section: Adriatic Seamentioning
confidence: 99%
“…The physicochemical processes are directly influenced by the inflow of water from the river Po in the north as well as its specific topography [35]. The Adriatic Sea has a lower salinity level than the rest of the Mediterranean due to the inflow of inland waters, which contain about a third of the freshwater that enters the entire Mediterranean Sea [35]. The eastern Balkan coast experienced a substantial warming of 1 • C between 1979 and 2015 [36].…”
Section: Adriatic Seamentioning
confidence: 99%
“…Being located in the northern limit of the Mediterranean latitudinal range, these areas are defined as "cul-de-sacs", from which cold-water species will have no possibility of escaping. Recent observational data showed that the AS, and in particular the NAS, is the sub-basin with the highest warming trend in sea surface temperature in the Mediterranean Sea over the last 20 years [27,64] (Figure A2), which could determine a strong reduction in cold-adapted species during the ongoing century and, in the worst case scenario, even their local extinction [29]. This phenomenon is probably occurring in the Adriatic population of whiting, whose distribution is restricted to the central and northern parts of the sub-basin, showing high abundance only in the northern part [39].…”
Section: Historical Comparisonmentioning
confidence: 99%